2017
DOI: 10.3892/mco.2017.1255
|View full text |Cite
|
Sign up to set email alerts
|

Curative effect of stereotactic body radiotherapy for unresectable massive primary liver cancer

Abstract: Abstract. The aim of this study was to evaluate the curative effect of gamma knife stereotactic body radiotherapy (SBRT) for unresectable massive primary liver cancer. A total of 69 patients with unresectable massive (>10 cm) primary liver cancer who were treated by SBRT at the Department of Radiation Oncology of the 323 Hospital of People's Liberation Army (Xi'an, China) between October, 2006 and October, 2010, were analyzed. According to the Union for International Cancer Control TNM staging guidelines, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Numerous retrospective studies have found SBRT to be safe and effective in both small HCC (<5 cm) (23-28) and large HCC (>10 cm) (29)(30)(31). Two-year LC, progressionfree survival, and OS rates ranged from 44-90% (32,33), 39-48% (24,34), and 24-67% (24,35), respectively.…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…Numerous retrospective studies have found SBRT to be safe and effective in both small HCC (<5 cm) (23-28) and large HCC (>10 cm) (29)(30)(31). Two-year LC, progressionfree survival, and OS rates ranged from 44-90% (32,33), 39-48% (24,34), and 24-67% (24,35), respectively.…”
Section: Retrospective Studiesmentioning
confidence: 99%